Exploring the Impact of Learning Activities on Self-efficacy in Academic Writing among Iraqi EFL Learners - Kamil, Ghada Kadhim (Celebes Scholar pg, 2024)
This study examined Iraqi EFL learners academic writing self-efficacy and learning practices. The research used purposive sampling to recruit 60 undergraduate and graduate students using a mixed method approach. Participants self-efficacy in academic writing is assessed using the validated Self-efficacy in Academic Writting Scale (SEAWS) and Self-efficacy questionnaire, instructors anonymous grading of relevant writing assignments. Participants experiences with learning activities and academic writing self-efficacy are explored in semi structured interviews. Social cognition theory and the model of writing self-efficacy served as the theoretical compass for this investigation. The research collects quantitative data from pre and post experiment surveys on self-efficacy and qualitative data from interviews to provide a complete picture. Data analysis used SPSS Software to analyze learning activities, self-efficacy, and academic writing performance. A statistically significant rise in participants self-efficacy after participating in learning activities was shown by results from pre and post questionnaire analyses (T = -2.37, p = 0.012*). Transcript thematic analysis reveals participant experiences patterns and themes. This research adds to the current body of knowledge by providing new insights into how learning activities affect the academic writing self-efficacy of Iraqi EFL learners.